2021
DOI: 10.3390/medicina57070654
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Resistance- and Endurance-Based Exercise Programs on Muscular Fitness, Body Composition, and Cardiovascular Variables in Young Adult Women: Contextualizing the Efficacy of Self-Selected Exercise Modalities

Abstract: There is an evident lack of research simultaneously investigating endurance training (ET) and resistance training (RT) with regard to their potential influence on fitness and health status in young women. This study aimed to determine the effects of RT and ET three times a week over an eight-week period on anthropometric/body composition indices, blood pressure (BP), and muscular fitness in apparently healthy young women who participated in a self-preferred program. The sample of participants comprised 57 youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Our finding on the independence of changes that occurred as a result of VE and PM actually implies that "individualization of the training" is not only a concept that should be respected in terms of "training load" (i.e., intensity or volume) but also a paradigm which should be valued in the process of selecting the training method (i.e., VE or PM). Although we could not find an empirical study that examined this issue in competitive athletes, the importance of an individualized approach in the application of self-preferred exercise modality has been confirmed in recent studies where recreational athletes were observed [40,41].…”
Section: Lack Of Association Between Changes In Performancesmentioning
confidence: 79%
“…Our finding on the independence of changes that occurred as a result of VE and PM actually implies that "individualization of the training" is not only a concept that should be respected in terms of "training load" (i.e., intensity or volume) but also a paradigm which should be valued in the process of selecting the training method (i.e., VE or PM). Although we could not find an empirical study that examined this issue in competitive athletes, the importance of an individualized approach in the application of self-preferred exercise modality has been confirmed in recent studies where recreational athletes were observed [40,41].…”
Section: Lack Of Association Between Changes In Performancesmentioning
confidence: 79%
“…Despite all of that, both aerobic and anaerobic physical exercise can increase the risk of overload and the risk of underdevelopment if not implemented properly in both children and adults [ 19 ]. On the other side, physical exercise will influence spatial coordination and orientation [ 20 , 21 ], next to muscular strength, speed, and aerobic resistance [ 22 ]. However, the motor abilities of young individuals are closely related to the physiological state, namely cardiac, respiratory, muscular, and nervous systems, along with height, body weight, body mass, and the level of physical exercise.…”
Section: Introductionmentioning
confidence: 99%